Anti-inflammatory evaluation of Scurrula ferruginea (jack) danser parasitizing on Tecoma stans (L.) H.B.K. in LPS/IFN-γ-induced RAW 264.7 macrophages. (25th March 2021) - Hong, Xia; Ajat, Mokrish; Fakurazi, Sharida; Noor, Akmal Mohd; Ismail, Intan Safinar
Abstract: Ethnopharmacological relevance: Scurrula ferruginea (Jack) Danser (locally known as 'Dedalu' or 'dian nan ji sheng' in Malaysia and China) is a hemi-parasitic shrub that is widely used as herbal medicine to treat inflammation, rheumatism, and stroke. However, the scientific basis of its anti-inflammatory function and mechanism remain to be proven. Aim of the study : To evaluate the anti-inflammatory activity as well as the preliminary mechanism of S. ferruginea parasitizing on Tecoma stans . Materials and methods: The anti-inflammatory capability of freeze-dried stem aqueous extract was assessed via inhibition of inflammatory cytokines interleukin- (IL-) 1 β, IL-6, IL-10, and tumor necrosis factor-alpha (TNF- α ) production in lipopolysaccharide (LPS) and interferon- γ (IFN- γ ) stimulated RAW 264.7 macrophages. The underlying anti-inflammatory mechanism was deciphered through reverse transcriptase and real time quantitative polymerase chain reactions (RT-PCR and qPCR) for inducible NO synthase ( i NOS), cyclooxygenase-2 (COX-2), IL-1 β, and TNF- α mRNA expression. Results: The results exhibited that aqueous extract of freeze-dried S. ferruginea stem sample concentration-dependently inhibited IL-1 β protein production along with the down regulation of i NOS and IL-1 β mRNA expression. Moreover, it significantly suppressed the protein release of IL-6 and IL-10 in a concentration-dependent manner. However, it slightly reduced TNF- α at higher sample concentration (250 μg/mL) without affecting the mRNA expression levels of COX-2 and TNF- α . Conclusions: This study suggests that S. ferruginea parasitizing on Tecoma stans exerted anti-inflammatory capability attributed to inhibition of i NOS and IL-1 β mRNA expression, NO creation, IL-1 β, IL-6, IL-10, and TNF- α protein production, indicating this plant might be a useful plant-derived candidate against inflammation. Graphical abstract: Image 1 Highlights: The anti-inflammatory effect in vitro of Scurrula ferruginea had been proven. S. ferruginea inhibited NO, IL-1 β, IL-6, IL-10, and TNF- α productions. Decrease of iNOS and IL-1β in LPS/IFN-γ induced RAW 264.7.